Strategi Pemasaran Produk Deposito pada BPRS Bumi Rinjani Kepanjen - Arinie Salsabiela Sufi; M. MANAN, YULIYANTI (Fakultas Ekonomi dan Bisnis, Universitas Islam Raden Rahmat Malang, 2025)
This study examines the marketing strategies employed for the iB BSR deposit product at BPRS Bumi Rinjani Kepanjen, amid intense competition from other financial institutions. Adopting a qualitative descriptive approach, data were collected through interviews, observations, and literature reviews. The findings reveal that the marketing strategy encompasses an inclusive target market determination, the application of the 4P marketing mix (product, price, place, promotion), and promotional efforts via social media, official websites, and direct services. The iB BSR deposit, grounded in a mudharabah mutlaqah contract, offers competitive profit-sharing ratios (31%-34%), flexible tenors (1, 3, 6, and 12 months), and security guaranteed by the Deposit Insurance Corporation (LPS). Supporting factors include customer trust and digital accessibility, while challenges involve limited customer education and competition from conventional banks. These findings are expected to enhance customer acquisition and strengthen BPRS Bumi Rinjani Kepanjen’s position in the Islamic banking market